If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2s+6)+5=s-27
We move all terms to the left:
3(2s+6)+5-(s-27)=0
We multiply parentheses
6s-(s-27)+18+5=0
We get rid of parentheses
6s-s+27+18+5=0
We add all the numbers together, and all the variables
5s+50=0
We move all terms containing s to the left, all other terms to the right
5s=-50
s=-50/5
s=-10
| 10m-17=71 | | (7+x)*5=20 | | 5x-7=4x+8= | | (7+x)x5=20 | | 2(8-h)-1=h-18 | | 3(r+1)+3=r-8 | | Y^2+23y+132=0 | | 5(n-2)-4=3(n+3)+1 | | 5(b-1)-4=3(b+2)-1 | | 5x+7/2=3/2x-18 | | 6+1,8x=15 | | 7(f-3)+1=f+16 | | 6x-11=61–3x= | | X2ª-5x+4=0 | | 2x-33=9x+7 | | x-45=5(x-2) | | 6x=25. | | x*x+x=52 | | -3=(p+3) | | 7x14=2x+11 | | 5x+x^2=52 | | 2x/3=357 | | 2(x+3)=3(5-x) | | x/5=42 | | 5x=4x10 | | 3+7x=-33+ | | 15x-20=-50 | | 7+m=4 | | 2x/1-x=0 | | 8x-2x-21=0 | | 4(x+3)=9x–10 | | 3+7x=44x+30 |